PerspektifInsider-Outsider dalam StudiAgama: Membaca Gagasan Kim Knott - Sujiat Zubaidi Saleh (Universitas Darussalam Gontor, 2010)
This article contains a study of Kim Knott which gives a new offer in religious study. This is due to many universities store a number of constraints surrounding the study of religion. In addition, the occurrence of methodology stagnant in the students circumstance in applying explorative studies about religion. In this study, Knott tries to take eliminate the subjectivity element by aparting two basic problems; between emic perspective appeared from the studies of insider, and ethical perspective from outsider. In the end, Knott divides roles conceptions in empowering the social religious interconections into four elements; the pure participant, the observer as participant, the participant as observer, dan the pure observer. However, this pattern turns out to save a serious problem in the benchmark objectivity. Because the issue is whether the observer from outsider is excatly objective, reliable, and has scientific validity seen from the view of insider. In this regard, Knott tries to put both frameworks in the rapprochement method. This approach is an intersubjective solution to give a position of observer in the margin of appreciation as the border line between insider-outsider. With this approach, the religious study is expected will be more objective and distant from the subjectivity element.